Simplifying
5b^2 + -5b + 1 = 0
Reorder the terms:
1 + -5b + 5b^2 = 0
Solving
1 + -5b + 5b^2 = 0
Begin completing the square. Divide all terms by
5 the coefficient of the squared term:
Divide each side by '5'.
0.2 + -1b + b^2 = 0
Move the constant term to the right:
Add '-0.2' to each side of the equation.
0.2 + -1b + -0.2 + b^2 = 0 + -0.2
Reorder the terms:
0.2 + -0.2 + -1b + b^2 = 0 + -0.2
Combine like terms: 0.2 + -0.2 = 0.0
0.0 + -1b + b^2 = 0 + -0.2
-1b + b^2 = 0 + -0.2
Combine like terms: 0 + -0.2 = -0.2
-1b + b^2 = -0.2
The b term is -1b. Take half its coefficient (-0.5).
Square it (0.25) and add it to both sides.
Add '0.25' to each side of the equation.
-1b + 0.25 + b^2 = -0.2 + 0.25
Reorder the terms:
0.25 + -1b + b^2 = -0.2 + 0.25
Combine like terms: -0.2 + 0.25 = 0.05
0.25 + -1b + b^2 = 0.05
Factor a perfect square on the left side:
(b + -0.5)(b + -0.5) = 0.05
Calculate the square root of the right side: 0.223606798
Break this problem into two subproblems by setting
(b + -0.5) equal to 0.223606798 and -0.223606798.
Subproblem 1b + -0.5 = 0.223606798
Simplifying
b + -0.5 = 0.223606798
Reorder the terms:
-0.5 + b = 0.223606798
Solving
-0.5 + b = 0.223606798
Solving for variable 'b'.
Move all terms containing b to the left, all other terms to the right.
Add '0.5' to each side of the equation.
-0.5 + 0.5 + b = 0.223606798 + 0.5
Combine like terms: -0.5 + 0.5 = 0.0
0.0 + b = 0.223606798 + 0.5
b = 0.223606798 + 0.5
Combine like terms: 0.223606798 + 0.5 = 0.723606798
b = 0.723606798
Simplifying
b = 0.723606798
Subproblem 2b + -0.5 = -0.223606798
Simplifying
b + -0.5 = -0.223606798
Reorder the terms:
-0.5 + b = -0.223606798
Solving
-0.5 + b = -0.223606798
Solving for variable 'b'.
Move all terms containing b to the left, all other terms to the right.
Add '0.5' to each side of the equation.
-0.5 + 0.5 + b = -0.223606798 + 0.5
Combine like terms: -0.5 + 0.5 = 0.0
0.0 + b = -0.223606798 + 0.5
b = -0.223606798 + 0.5
Combine like terms: -0.223606798 + 0.5 = 0.276393202
b = 0.276393202
Simplifying
b = 0.276393202
SolutionThe solution to the problem is based on the solutions
from the subproblems.
b = {0.723606798, 0.276393202}
2007-01-25 03:04:02
·
answer #1
·
answered by SHIBZ 2
·
0⤊
0⤋
well I hope this is easy for you.
let us use completing the square method
5b^2 - 5b + 1 = 0
1) separate the constant term 1
5b^2 -5b = -1
2) divide both sides by 5
b^2 - b = -1/5
3) complete the square for b
b^2 -b + 1/4 = -1/5 + 1/4
1/4 happens to be that term that could make the left member perfect square.
4) factor the left side and simplify the fraction on the right side
( b - 1/2)^2 = 1/20
5) take square root both sides
( b - 1/2) = + or - (square root of 5) / 10
6) transpose 1/2
b = 1/2 + or - (square root of 5 )/ 10
7) or better yet
b = 5 + or - (the square root of 5) / 10
2007-01-25 00:05:02
·
answer #2
·
answered by thegrouch 2
·
0⤊
0⤋
5b^2 – 5b + 1 = 0 …………………….(1)
Compare this quadratic equation with this basic quadratic equation:-
aX^2 + bX + c = 0 …………………….(2)
In this case, b from first equation is same as X in the second equation.
We have to use the following formula to solve for b from first equation:-
X = [- b ± â (b^2 – 4ac)] / [2a]
From first equation:-
a = 5
b = -5
c = 1
Substitute all the values of a, b, and c into the given formula:-
X= [- (-5) ± â ({-5} ^2 – 4*5*1)] / [2*5]
= [5 ± â (25– 20)] / [10]
= [5 ± â (5)] / [10]
= [5 + â (5)] / [10] or [5 - â (5)] / [10]
= 0.723606797 or 0.276393202
So the solution for b that you looking for is b = X = 0.723606797 or 0.276393202
2007-01-25 00:32:49
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
You will really need to use the quadratic formula...I can't show you the work on here due to computer functionality...the formula is -b plus or minus the square root of b squared-4(a)(c) all over 2a...just a hint, though. your negative b at the beginning will be a positive 5, because your b of abc for the formula is -5 and when you have a negative and negative, it becomes positive. Much luck!
2007-01-24 23:53:01
·
answer #4
·
answered by Kaylin 4
·
1⤊
0⤋
Assuming that when you said 5b squared you meant 5b^2...
First subtract 1 from both sides.
5b^2 - 5b = -1
Then,
5b(b-1) = -1
or
5(b^2-b) = -1
Divide
b^2-b= -1/5
b(b-1)= -1/5
i don't know what next, sorry lol.
2007-01-24 23:50:12
·
answer #5
·
answered by quarters 2
·
0⤊
1⤋
is it (5b)^2
or
5 (b^2)
?
it could be 1 or -1/5
2007-01-24 23:52:11
·
answer #6
·
answered by Poutine 7
·
1⤊
1⤋
(-b +or- root(b^2-4ac))/(2a)
(5 +- root(25-4*5*1))/(10)
b=(5 -root5)/10 or (5+root5)/10
dont listen to them, its deffinately not 1. test it
2007-01-24 23:52:20
·
answer #7
·
answered by jcj7373 2
·
1⤊
1⤋
look up the quadratic equation on the internet and use that. it is fairly easy
2007-01-24 23:47:20
·
answer #8
·
answered by bob fuller 1
·
1⤊
1⤋
5b²-5b+1=0
5b²-5b=-1
5b²=5b-1
b²=(5b-1)/5
b=â((5b-1)/5)
2007-01-24 23:49:25
·
answer #9
·
answered by curious george 4
·
0⤊
2⤋
.7236068
2007-01-25 00:00:43
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋